The Impact of Job Satisfaction, Organizational Commitment, and Perceived Organizational Support on Employee Motivation: The Case of Public Agencies in Azerbaijan - Kazimzada, Shalala (ADA University, 2025)
This study investigates the impact of Job Satisfaction (JS), Organizational Commitment (OC), and Perceived Organizational Support (POS) on Employee Motivation (EM) in the public sector of Azerbaijan. Guided by established theories, including Herzberg’s Motivation–Hygiene Theory, Self-Determination Theory, Organizational Support Theory, and the Three-Component Model of Organizational Commitment, the research aims to determine both the direct and indirect effects of these factors on motivation. Data were collected through a survey of 311 employees across five public institutions in Baku. Using regression and mediation analyses, four hypotheses are tested. The results confirm that each factor has a significant positive association with EM when examined independently. However, in the joint model, only OC and POS remain significant predictors, while JS loses its independent effect. Mediation analyses reveal that JS influences EM indirectly through OC, indicating that satisfaction enhances motivation primarily by fostering commitment. POS, meanwhile, demonstrates both direct effects on EM and indirect effects through OC, including a serial pathway via JS and OC, highlighting its key role in sustaining motivation. Overall, the three predictors together explain 36% of the variance in EM. Among demographic controls, age was negatively associated with motivation, while gender and tenure are not significant. These findings demonstrate that in Azerbaijan’s public sector, EM is shaped less by routine job satisfaction and more by relational and organizational factors, particularly employees’ loyalty and their perceptions of support. The study contributes to theory by clarifying the mediating role of OC, provides practical insights for managers seeking to strengthen motivation through supportive practices, and informs policy by emphasizing the importance of organizational fairness and recognition in resource-constrained environments.
Keywords: Employee motivation -- Public sector -- Azerbaijan.; Job satisfaction -- Influence on employee motivation.; Organizational commitment -- Effect on motivation.; Perceived organizational support -- Effect on employee motivation.